2022
DOI: 10.53075/ijmsirq/45645464535
|View full text |Cite
|
Sign up to set email alerts
|

Rural/Urban Variations in Diabetes Self-Care in a Sample of Ghanaian Adults with Type II Diabetes: a Study in the East Gonja Municipality

Abstract: More recently, there has been a greater focus on nutrition and physical activity as key determinants of health. Available evidence suggests that community of residence drive unhealthy diets and sedentary behaviour (e.g. increased physical inactivity); unhealthy diet and sedentary behaviour are major risk factors for non-communicable diseases (NCDs). This single-site hospital-based study assessed rural/urban variations in diabetes self-care practices in a sample of Ghanaian adults with type II diabetes. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The highest optimal proportion of adherence (84.5%) was reported by Afaya et al [23] and the lowest (33.5%) by Kretchy et al [16]. Three studies found optimal adherence to medication to be prevalent in more than half of the participants [8,23,30].…”
Section: Medicationmentioning
confidence: 93%
See 4 more Smart Citations
“…The highest optimal proportion of adherence (84.5%) was reported by Afaya et al [23] and the lowest (33.5%) by Kretchy et al [16]. Three studies found optimal adherence to medication to be prevalent in more than half of the participants [8,23,30].…”
Section: Medicationmentioning
confidence: 93%
“…Further, Mogre et al [27] reported the daily adherence to recommendations on physical activity to be 21.4% among participants. The overall adherence to physical activity reported by Nketia [30] was 41.8%.…”
Section: (216)mentioning
confidence: 95%
See 3 more Smart Citations